STUDENTS’ ATTITUDE TOWARDS ASSIGNMENT AND ASSESSMENT IN READING: AN OVERVIEW OF E-LEARNING - Setiana Sri Wahyuni Sitepu (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
Abstract E-learning is a program that has been implemented in Pamulang University since 2015. Despite the benefits of it as the medium for the students to learn with the absence of the teacher, it also gives beneficial or them to learn independently and creatively. However, as it is a latest for both teachers and students, the adversity cannot be avoided in terms of assignments and assessments. Therefore, this study was aimed to reveal the students’ attitude towards the assignments and assessments provided by the teacher for Reading in E-learning Program. The participants of this study were 40 students of reading class at the fourth semester of English Department of Faculty of Letters of Pamulang University. The data were collected by questionnaires and observation that the questionnaires were given to the students of reading subject while observation was conducted by observing reading assignment and assessment of E-learning program. The data from observation were analyzed by using qualitative measurement and the questionnaire used paper-based Likert-scale. The results showed that in spite of the difficulties in adapting in E-learning program they also have difficulties in understanding the materials and term of assessment. Furthermore, there is a negative attitude from them toward the assignment and assessment of reading in E-learning program.Keywords:, assignment, assessment, attitude, e-learning, reading